Right ventricular outflow tract ablation associated with anomalous origin of coronary artery: A “double-edged sword” - Fernández Prado, Hael Lizandro (2024)
Catheter ablation is a curative and effective therapeutic option for idiopathic and symptomatic right ventricular outflow tract (RVOT) ventricular tachycardia (VT). However, cases of coronary artery injury during catheter ablation have been reported. 2, 3, 4 Anomalous aortic origin of the coronary artery (AAOCA) is a rare condition, usually associated with an abnormal trajectory of the involved vessels, being a “double-edged sword,” depending on whether the coronary artery is distant or close to the site of origin of the VT. Therefore, in these cases it is essential to determine the relationship between these structures to avoid iatrogenic damage to the epicardial vessels. There is only one reported case of successful ablation of RVOT VT in a patient with an anomalous aortic origin of right coronary artery (R-AAOCA), in which the artery ran very close to the ablation site (risk factor for coronary artery injury). We present this exceptional case of L-AAOCA that resulted as a protective factor during successful radiofrequency cardiac ablation (RFCA) of symptomatic RVOT VT.